Economic impacts of decarbonizing the Swiss passenger transport sector - Vanessa Angst; Chiara Colesanti Senni; Markus Maibach; Martin Peter; Noe Reidt; Renger van Nieuwkoop (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
Switzerland committed to achieving net-zero emissions in 2050. This goal is particularly ambitious for the Swiss passenger transport system, which emits more than one third of Swiss CO2 emissions, and is not yet on a clear emission reduction path. We investigate the economic impact and the emission-saving potential of a decarbonization pathway for the Swiss transport sector based on three edge case scenarios and on a combination of them: (1) improved fuel/engine technology and fostered diffusion of battery electric vehicle, (2) increased capacity use of passenger cars, and (3) enhanced modal shift towards public transport. Our analysis is conducted using a multi-model framework, which interlinks a computational general equilibrium model with two external transportation models. This approach allows us to incorporate a highly disaggregated passenger transport system into the economic analysis. The framework is calibrated to Swiss data to assess the optimal scenario mix in terms of emissions and economic impact. The optimal decarbonization pathway mix slightly increases welfare and lowers CO2 emissions of passenger transport in 2050 from 6 to 1.7 million tons CO2 compared to the reference scenario. Despite the sharp reduction in emissions, a decarbonization pathway based on the considered scenarios is insufficient to reach the net-zero emission target.
Keywords: C68; R40; R42; R48; 330; Passenger transport; Decarbonization; Switzerland; Computable general equilibrium model